Предмет: Алгебра,
автор: malikovamirxon07
cos22°+cos24°+cos26°+cos28°
Ответы
Автор ответа:
1
cos 22° + cos 24° + cos 26° + cos 28° = (cos22°+cos28°)+(cos24°+cos26°)=
=2cos((22°+28°)/2)•cos((28°-22°)/2)+2cos((24°+26°)/2)•cos((26°-24)°/2)=
2cos25°•cos3° + 2cos25°•cos1° = 2cos25(cos3°+cos1°)=2cos25°•2cos((3°+1°)/2)•cos((3°-1°)/2)=
=4cos25°•соs2°•cos1°
=2cos((22°+28°)/2)•cos((28°-22°)/2)+2cos((24°+26°)/2)•cos((26°-24)°/2)=
2cos25°•cos3° + 2cos25°•cos1° = 2cos25(cos3°+cos1°)=2cos25°•2cos((3°+1°)/2)•cos((3°-1°)/2)=
=4cos25°•соs2°•cos1°
Похожие вопросы
Предмет: Математика,
автор: matvijpetruk03
Предмет: Математика,
автор: imrona12345
Предмет: Алгебра,
автор: lerazu961
Предмет: Музыка,
автор: Аноним